A large-scale intervention to introduce orange sweet potato in rural Mozambique increases vitamin A intakes among children and women - Hotz, C.; Loechl, C.; de Brauw, Alan; Eozenou, P.; Gilligan, Daniel O.; Moursi, M.; Munhaua, B.; Jaarsveld, P.J. van; Carriquiry, A.; Meenakshi, J.V. (Cambridge University Press, 2012)
β-Carotene-rich orange sweet potato (OSP) has been shown to improve vitamin A status of infants and young children in controlled efficacy trials and in a small-scale effectiveness study with intensive exposure to project inputs. However, the potential of this important food crop to reduce the risk of vitamin A deficiency in deficient populations will depend on the ability to distribute OSP vines and promote its household production and consumption on a large scale. In rural Mozambique, we conducted a randomised, controlled effectiveness study of a large-scale intervention to promote household-level OSP production and consumption using integrated agricultural, demand creation/behaviour change and marketing components. The following two intervention models were compared: a low-intensity (1 year) and a high-intensity (nearly 3 years) training model. The primary nutrition outcomes were OSP and vitamin A intakes by children 6–35 months and 3–5·5 years of age, and women. The intervention resulted in significant net increases in OSP intakes (model 1: 46, 48 and 97 g/d) and vitamin A intakes (model 1: 263, 254 and 492 μg retinol activity equivalents/d) among the younger children, older children and women, respectively. OSP accounted for 47–60 % of all sweet potato consumed and, among reference children, provided 80 % of total vitamin A intakes. A similar magnitude of impact was observed for both models, suggesting that group-level trainings in nutrition and agriculture could be limited to the first project year without compromising impact. Introduction of OSP to rural, sweet potato-producing communities in Mozambique is an effective way to improve vitamin A intakes.